Experimental Study on Pressure Relief Gas Extraction of Goaf with Large Diameter Borehole inHigh Gas Close Distance Coal Seams - SHAO Guoan, ZOU Yongming (Meikuang Anquan, 2020)
Based on the engineering background of gas control in the close distance coal seams goaf in Xiaohuigou Coal Mine, the experimental study on the pressure relief gas extraction of goaf with the large diameter borehole in close distance coal seams is carried out combined with the theoretical analysis and field test, and the principle of the large diameter borehole extraction pressure relief gas of the goaf was studied, the field tests were carried out in the 2201 first working face. The field results show that the influence range of one large diameter drilling is 30-50 m, the net flow of a large diameter borehole is equivalent to that of 580 small diameter holes, the total amount of gas extraction is 701 120.67 m3, the average gas extraction concentration is 2.24%, the average mixed extraction flow is 166.3 m3/min, the maximum gas concentration of the upper corner is 0.67%, the maximum daily output of the working face is 9 370 t, which can ensure the gas control of the goaf in the initial pressure stage of the working face, and provides a reference for the gas control of the goaf under similar conditions.